2023
DOI: 10.1292/jvms.22-0563
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> chondrotoxicity of bupivacaine, levobupivacaine and ropivacaine and their effects on caspase activity in cultured canine articular chondrocytes

Abstract: Bupivacaine, levobupivacaine and ropivacaine are potent, long acting, amide-type local anesthetics that have several clinical applications including intra-articular administration. The objectives of this study were to evaluate their in vitro effects on cell viability and caspase activity to elucidate whether they activate the extrinsic or intrinsic pathways of apoptosis in canine articular chondrocytes.Chondrocytes in monolayer culture were treated with culture medium as the control, or with 0.062% (0.62 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Research suggests that their application could induce cell death and structural changes in the articular cartilage in a matter of weeks [ 8 ]. Recent in vitro research by Mwale et al in 2023 found that bupivacaine, levobupivacaine, and ropivacaine triggered apoptosis, as indicated by increased caspase-3 activity, within 24 h of induction of the drug [ 9 ]. Properly evaluating the balance between short-term pain relief benefits and potential long-term cartilage risks is essential when considering what combination of IA injections to utilize.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that their application could induce cell death and structural changes in the articular cartilage in a matter of weeks [ 8 ]. Recent in vitro research by Mwale et al in 2023 found that bupivacaine, levobupivacaine, and ropivacaine triggered apoptosis, as indicated by increased caspase-3 activity, within 24 h of induction of the drug [ 9 ]. Properly evaluating the balance between short-term pain relief benefits and potential long-term cartilage risks is essential when considering what combination of IA injections to utilize.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the sentence in the introduction highlighted by Dr. Raghuraman could be confusing. It would be more accurate to state that numerous meta-analyses have examined different facets of laparoscopic cholecystectomy [3], and a subset of them have placed a specific emphasis on pain management and analgesic needs.…”
Section: Anjumentioning
confidence: 99%
“…Therefore, ropivacaine would have been a better choice for this study, especially at such high doses. Additionally, the authors could have followed up with their patients for chondrotoxicity, which would have added more evidence regarding this LA associated side effect [ 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation